STRATEGI MEMBAGUN KEUNGGULAN BERSAING PADA LEMBAGA PENDIDIKAN - Tantohadi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
In the midst of intense competition among educational institutions, strategic efforts are the key to the success of institutions in maintaining their existence and appeal to the public. One of the strategies that can be employed is the development of the institution's image. The success of implementing this strategy depends on a deep understanding of the institution's internal and external conditions. The importance of selecting the right method in line with the institution's situation and condition becomes a crucial factor in building a positive image among both internal and external stakeholders. Educational institutions need to identify their positioning, brand value, and appropriate concepts to create a strong and convincing image. Furthermore, institutions must highlight specific values that can be leveraged as a competitive advantage in the competition with other institutions. By implementing the right strategies and promoting these values of excellence, educational institutions can achieve high-quality education and enhance their competitiveness in the market. Overall, successful image development requires a holistic and sustainable approach. Thus, educational institutions can maintain their existence amidst increasingly fierce competition and continue to be sought after by the public.